Relationship of Body Size to Metabolic Markers and Left Ventricular Hypertrophy in Cats. (20th November 2014) - Freeman, L.M.; Rush, J.E.; Feugier, A.; van Hoek, I.
<x xml:space="preserve">Abstract</x> Background Cats with hypertrophic cardiomyopathy (HCM) are larger and have higher insulin‐like growth factor‐1 (IGF‐1) concentrations than cats without HCM. Hypothesis/Objectives The aim of this study was to assess echocardiographic findings in a colony of adult cats to determine the relationship between early growth and left ventricular hypertrophy (LVH). Animals Twenty‐eight neutered adult cats (20 males, 8 females) from a colony ≥3 years of age for which growth curves were available. Methods Case–control study. Physical examination and echocardiography were performed, and body weight, body condition score (BCS), and head length and width were measured. Circulating glucose, insulin, N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP), and IGF‐1 concentrations were measured and growth data were collected. Stepwise multivariate analyses were performed. Results Mean age was 5.2 ± 1.1 years. Current BCSs ranged from 4 to 9 (median, 6) and mean body weight was 4.88 ± 1.29 kg. Variation in body weight was apparent by 6 (mean = 3.26 ± 0.80 kg) and 12 months of age (mean = 4.02 ± 1.02 kg). Cardiac abnormalities included a cardiac murmur (n = 7; 24%), gallop (n = 3; 10%), and arrhythmia (n = 1; 4%). Fourteen of 28 cats (50%) had echocardiographic evidence of LVH. Head width (P = .017), body weight (P < .001), NT‐proBNP (P = .023), and IGF‐1 (P = .013–.022) were significantly associated with selected measures of LVH. Conclusions and Clinical Importance Potential associations between body size, IGF‐1, LVH, and HCM warrant future prospective studies.